A Study on the Effectiveness of “Production-Oriented Approach” in College English Integrated Courses -- Taking Art Students in Ordinary Universities as the Object of Study - Wang, Xueqing (Pacific International Journal, 2023)
Based on the theory of “Production-Oriented Approach”, our team carried out a teaching experiment of college English integrated course among art students in our university. The results of this “Production-Oriented Approach” teaching experiment show that “Production-Oriented Approach” teaching can effectively improve students' overall English level, especially students' speaking and writing ability, and promote the improvement of students' language output level; “Production-Oriented Approach” is deeply loved by students, which enhances their English learning motivation, their confidence in English learning, and their learning autonomy.